Leptostracans (Crustacea: Phyllocarida) from mud volcanoes at the Gulf of Cadiz (NE Atlantic) with description of a new species of Sarsinebalia Dahl, 1985 - Moreira, Juan; Esquete, Patricia; Cunha, Marina R. (European Journal of Taxonomy, 2021)
Three leptostracan species (Crustacea: Phyllocarida) are reported from mud volcanoes at the Moroccan margin of the Gulf of Cadiz (NE Atlantic). Nebalia strausi Risso, 1826 and N. abyssicola Fage, 1929 were found in experimentally deployed organic substrates in Mercator, Meknès and Darwin mud volcanoes; N. abyssicola was also found among bathymodiolin bivalves and is recorded for the first time in the Atlantic Ocean. The third species was collected from the Gemini mud volcanoes and is described herein as Sarsinebalia ledoyeri sp. nov. The new species is characterised by having the eyes provided with ommatidia and lacking pigment, the ventral margin of the eye is concave along distal half, the antennular scale is more than twice as long as wide, the second article of the mandibular palp bears one seta on lateral surface about 0.5 times as long as the article and one subterminal seta longer than the third article, the distal article of the maxilla II endopod is about 1.8 times as long as the proximal article, the maxilla II exopod is clearly longer than the endopod proximal article, the lateral margin of the pleopod I exopod lacks setae and the posterodorsal border of pleonites VI–VII is provided with rounded to pointed denticles.